Amaranth selective hydrolyzed protein influence on sourdough fermentation and wheat bread quality. Issue 12 (13th October 2021) - Karimi, Nayereh; Zeynali, Fariba; Rezazad Bari, Mahmoud; Nikoo, Mehdi; Mohtarami, Forogh; Kadivar, Mahdi
Abstract: Amaranth selective hydrolyzed protein (ASPH) may improve sourdough properties and bread quality. In this regard, this study focused on investigating the influence of protein hydrolysates on sourdough fermentation and bread properties. Based on the findings, ASPH further increased Lactobacillus plantarum and Saccharomyces cerevisiae growth in sourdough compared with amaranth protein isolates and amaranth flour. ASPH at 5 g/kg resulted in sourdough with higher pH and total titratable acidity (TTA) after 20 h of fermentation at 30°C. The prepared sourdough using APH (S‐ASPH) at 3 g/kg increased the specific volume (4.57 ml/g) and TTA (4.76 ml) while decreasing water activity, hardness, cohesiveness, and chewiness of the bread (S‐ASPH‐B) compared with the control. Moreover, transition temperature and enthalpy reduced whereas sensory properties and shelf life represented an increase with S‐ASPH addition. Overall, the obtained data indicated the improvement of bread quality by S‐ASPH sourdough. Abstract : Our results indicated the improvement of bread quality by sourdough prepared with amaranth protein hydrolysates. ASHP might be useful as natural ingredients of sourdough and wheat bread.